2010
DOI: 10.1177/1090820x10386929
|View full text |Cite
|
Sign up to set email alerts
|

Subcutaneous Temporal Browlift Under Local Anesthesia: A Useful Technique For Periorbital Rejuvenation

Abstract: The subcutaneous temporal brow lift is an effective, reproducible, and inexpensive technique that can be performed safely under local anesthesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 9 publications
0
28
0
Order By: Relevance
“…The technique used in this case series proposes the option of fast, efficient results and at low cost due to the absence of hospitalization and conditions linked to the use of general anesthesia. It has been confirmed that with this lateral access technique there is a smaller but more comfortable dissection and with a lower level of nerve damage (Bidros et al 2010;Taban, 2016). For the patient, the reduction in costs and anxiety is significant, so that techniques like these are not so frequently rejected because of the increased benefits they offer.…”
Section: Discussionmentioning
confidence: 90%
“…The technique used in this case series proposes the option of fast, efficient results and at low cost due to the absence of hospitalization and conditions linked to the use of general anesthesia. It has been confirmed that with this lateral access technique there is a smaller but more comfortable dissection and with a lower level of nerve damage (Bidros et al 2010;Taban, 2016). For the patient, the reduction in costs and anxiety is significant, so that techniques like these are not so frequently rejected because of the increased benefits they offer.…”
Section: Discussionmentioning
confidence: 90%
“…(8) However, the effects of subcutaneous dissection are not lasting, and a second temporal facelift is often needed for sustained results. (9) These days, detachment in the temporal area is more commonly performed in the subgaleal plane. (10,11) However, the rejuvenation effect is compromised when dissection is carried out in only one plane.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, this procedure is particularly useful in brows asymmetry because it assures an high degree of control on the vector and extent of the lifting. 1 In other techniques, where a more extensive dissection is needed (coronal approach [19][20][21] temporal approach), with Endotine device 10,11,21,22 or suture technique fixation, 23 the edema and the indirect visualization together with the length of the anchorage Pair ¼ comparison; C1-C2: pre-and postoperative position of central eyebrow respect to interpupillary line; L1-L2: pre and postoperative position of lateral eyebrow respect to interpupillary line; M1-M2: pre and postoperative position of medial eyebrow respect to inter-pupillary line; Mean, mean differences; Std, standard; t, test statistical t; df, degree of freedom (nÀ1); Sig., statistical significance (P < 0.05). Pair ¼ comparison; C1-C2: pre-and postoperative position of central eyebrow respect to interpupillary line; L1-L2: pre and postoperative position of lateral eyebrow respect to interpupillary line; M1-M2: pre and postoperative position of medial eyebrow respect to inter-pupillary line; Mean, mean differences; Std, standard; t, test statistical t; df, degree of freedom (nÀ1); Sig., statistical significance (P < 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…The associated presence of forehead rhytids, the position of the anterior hairline and, first of all, the brow's symmetry are essential elements for surgical planning. 1 The weakness of the adhesion and subsequent sliding of the lateral third of the brow, enhanced by the movement of the lateral portion of the orbicularis oculi muscle, as well as the patient's genetic, are responsible of eyebrow's descent and of the alterations in the skin and soft tissues in this area. The lateral brow ptosis compromises the classic shape of this essential element in facial configuration, resulting in an aged appearance, 2 a sad and tired look and a pseudo excess in the skin of the upper eyelid.…”
mentioning
confidence: 99%